VC visits Selayang & Sg. Buloh - Mohd Yusof, Nur Yusrina (Faculty of Medicine, 2021)
On 26 October 2021 and 5 November 2021, the Vice-Chancellor of Universiti Teknologi MARA (UiTM), Prof. Ts. Dr. Hajah Roziah Mohd Janor, conducted official visits to the Faculty of Medicine at the Selayang and Sungai Buloh campuses, respectively. During these visits, a comprehensive briefing was delivered by Prof. Dr. Effat Omar, Acting Dean of the Faculty of Medicine. To ensure inclusivity, the sessions were broadcast live, enabling all staff and students to participate virtually.